2017
DOI: 10.1515/acve-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro and in Vivo Anti-Cancer Potential of Mycobacterium Cell Wall Fraction (MCWF) Against Canine Transitional Cell Carcinoma of the Urinary Bladder

Abstract: Transitional cell carcinoma (TCC), is the most common form of urinary bladder cancer in dogs and represents 2% of all reported canine cancers. Canine TCC is usually a high-grade invasive cancer and problems associated with TCC include urinary tract obstruction and distant metastases in more than 50% of affected dogs. TCC is most commonly located in the trigone region of the bladder precluding complete surgical resection. Current treatment options for TCC in dogs include medical therapy, surgery or radiation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
(62 reference statements)
2
9
0
Order By: Relevance
“…Amplimune also induced increases in total WBC count in heifers when administered via SC or IM injection at a dose rate of 2 mL; and increases in lymphocyte counts in heifers when administered via SC or IM injection at a dose rate of 5 mL. In other studies investigating MCWF, from non‐Amplimune sources, in mice, 47 dogs 48 and horses, 49 changes have been observed in a variety of parameters. Activation of cytotoxic T‐cells by MCWF induced the reduction of three different cancer cell lines in mice tumours 47 ; clinical symptoms of bladder cancer, including dysuria, pollakiuria and haematuria, were reduced following administration of MCWF in dogs 48 ; and a reduction in the number of mares positive for endometritis, based on exfoliative cytology and bacteriology, when administered MCWF at 48 h post‐experimental challenge 49 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Amplimune also induced increases in total WBC count in heifers when administered via SC or IM injection at a dose rate of 2 mL; and increases in lymphocyte counts in heifers when administered via SC or IM injection at a dose rate of 5 mL. In other studies investigating MCWF, from non‐Amplimune sources, in mice, 47 dogs 48 and horses, 49 changes have been observed in a variety of parameters. Activation of cytotoxic T‐cells by MCWF induced the reduction of three different cancer cell lines in mice tumours 47 ; clinical symptoms of bladder cancer, including dysuria, pollakiuria and haematuria, were reduced following administration of MCWF in dogs 48 ; and a reduction in the number of mares positive for endometritis, based on exfoliative cytology and bacteriology, when administered MCWF at 48 h post‐experimental challenge 49 .…”
Section: Discussionmentioning
confidence: 84%
“…In other studies investigating MCWF, from non-Amplimune sources, in mice, 47 dogs 48 and horses, 49 changes have been observed in a variety of parameters. Activation of cytotoxic T-cells by MCWF induced the reduction of three different cancer cell lines in mice tumours 47 ; clinical symptoms of bladder cancer, including dysuria, pollakiuria and haematuria, were reduced following administration of MCWF in dogs 48 ; and a reduction in the number of mares positive for endometritis, based on exfoliative cytology and bacteriology, when administered MCWF at 48 h postexperimental challenge. 49 In these studies, immune activation was induced without excessive inflammation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…MCWF also has potential for use in other veterinary applications, such as the treatment of infectious diseases [11][12][13] and the treatment of cancer. 10,14 The mode of action of MCWF is based on the activation of innate and adaptive immunity 15 with the purpose of the recognition of, reaction to, and quick recovery from infections. 10,11,13 Previous studies have demonstrated that subcutaneous administration of MCWF in day-old calves resulted in decreased morbidity, decreased treatment costs and increased average daily gain.…”
Section: Introductionmentioning
confidence: 99%